Reestructuración técnica, comercial y administrativa de la empresa soluciones lógicas Yayan Gaia (2018)
A restructuring study was developed for the company ‘Soluciones lógicas Yayan Gaia‘ which initially applied a diagnostic study, identifying the current state of the company and the different factors that affect it; An analysis was made out with the tool proposed by the Chamber of Commerce, identifying key elements for the proper development of the organization; following this with a market study, which indicated relevant components for the marketing of the service, started with a study of the sector's analysis, identified barriers to entry, segment the market, identified customers in the Bogotá City.